2014
DOI: 10.1002/elps.201400040
|View full text |Cite
|
Sign up to set email alerts
|

The free solution mobility of DNA and other analytes varies as the logarithm of the fractional negative charge

Abstract: The free solution mobilities of single- and double-stranded DNA molecules with variable charge densities have been measured by capillary electrophoresis. DNA charge density was modified either by appending positively or negatively charged groups to the thymine residues in a 98 base pair (bp) DNA molecule, or by replacing some of the negatively charged phosphate internucleoside linkers in small single-or double-stranded DNA oligomers with positively charged phosphoramidate linkers. Mobility ratios were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Two 98 bp DNA oligomers, one containing 4 in-phase (ds98-4in) and one with 4 out-of-phase (ds98-4out) A 6 -tracts, were used to determine the effect of different monovalent cations on A-tract-induced curvature [82,83]. The mobilities observed for ds98-4in in low ionic strength BGEs were significantly lower than observed for ds98-4out, both in free solution and in polyacrylamide gels, as shown in Fig.…”
Section: A-tract-induced Curvaturementioning
confidence: 99%
See 1 more Smart Citation
“…Two 98 bp DNA oligomers, one containing 4 in-phase (ds98-4in) and one with 4 out-of-phase (ds98-4out) A 6 -tracts, were used to determine the effect of different monovalent cations on A-tract-induced curvature [82,83]. The mobilities observed for ds98-4in in low ionic strength BGEs were significantly lower than observed for ds98-4out, both in free solution and in polyacrylamide gels, as shown in Fig.…”
Section: A-tract-induced Curvaturementioning
confidence: 99%
“…(1). To compare the mobilities of ss-and dsDNAs with different charge densities, measured on different days in different BGEs, mobility ratios were calculated for each data set by dividing the mobility of each charge variant by the mobility of its fully charged, unmodified parent DNA, measured under the same experimental conditions [83,124]. The mobility ratios were then plotted as a function of the fractional charge of the charge variant.…”
Section: Dependence Of Dna Mobility On Charge Densitymentioning
confidence: 99%
“…The decreased mobility is due to the preferential localization of monovalent cations in the A-tract minor groove, because no mobility decrease is observed if the minor groove is blocked by the binding of netropsin (46). We have also characterized the dependence of DNA electrophoretic mobilities on the ionic strength of the solution and the charge density of the polyion (49)(50)(51). Finally, we showed that the curvature of A-tract-containing DNA molecules is markedly reduced in solutions containing~200 mM cation, even though monovalent cations are still preferentially localized in the A-tract minor groove (19).…”
Section: Introductionmentioning
confidence: 97%
“…We have been using free-solution capillary electrophoresis (CE) to evaluate the properties of small ssDNA and dsDNA in solutions containing various monovalent cations. Our previous studies have addressed the dependence of the electrophoretic mobility of DNA on molecular weight (22)(23)(24), ionic strength (25,26), curvature (27)(28)(29)(30), charge density (23,(30)(31)(32), and solution viscosity (33). Here, we have used CE to determine the dependence of the electrophoretic mobility of ssDNA and dsDNA on ionic strength in solutions containing high concentrations of Na þ ions.…”
Section: Introductionmentioning
confidence: 99%